Divergence Between Informant and Self-Ratings of Activities of Daily Living Impairments in Parkinson’s Disease - Becker, Sara; Solbrig, Susanne; Michaelis, Katja; Faust, Bettina; Brockmann, Kathrin; Liepelt-Scarfone, Inga (Frontiers in Aging Neuroscience, 2022)
Objective To examine the agreement between self- and informant-reported activities of daily living (ADL) deficits in Parkinson’s Disease (PD) patients, and to examine factors influencing ADL ratings. Background In PD, the loss of functional independence is an important outcome of disease progression. The valid assessment of ADL function in PD is essential, but it is unclear to what extent informants’ and patients’ perceptions of their daily functions concur, and how other factors may influence both ratings. Methods Data of 150 PD patients who underwent cognitive and motor testing, as well as their informants were analyzed. The 10-item Functional Activities Questionnaire (FAQ), completed separately by patients (FAQ-S) and their informants (FAQ-I), assessed ADL function. Weighted κ statistics summarized level of agreement, and a discrepancy score (FAQ-I – FAQ-S) quantified agreement. Correlation analyses between FAQ total scores, patient and informant characteristics, and cognitive scores were conducted, with post hoc regressions to determine the associations between both FAQ scores and cognition, independent of patient characteristics. Results The sample included 87 patients with normal cognition, 50 with mild cognitive impairment, and 13 with dementia. Overall, there was fair to moderate agreement between patients and informants on individual FAQ items (0.27 ≤ κ ≤ 0.61, p < 0.004), with greater discrepancies with increasing cognitive impairment. Patients’ age, motor severity, non-motor burden, and depression also affected both ratings (0.27 ≤ r ≤ 0.50, p < 0.001), with motor severity showing the greatest influence on both ratings. Both the FAQ-I and FAQ-S were correlated with almost all cognitive domains. Post hoc regression analyses controlling for patient characteristics showed that the attention domain was a significant predictor of both the FAQ-S and FAQ-I scores, and memory was also a significant predictor of the FAQ-I score. Only 29.3% of patients agreed perfectly with informants on the FAQ total score, with informants most commonly rating ADL impairments as more severe than patients. Conclusions Patient and informant ratings of ADL function using FAQ items showed moderate agreement, with only few items reaching substantial agreement. Ratings of both were associated with patient cognitive status, but also other characteristics. In addition to patient and informant reports, objective measures are needed to accurately classify ADL deficits in PD.